Study on the Mechanism of Tooth Tissue Repair Based on Stem Cell Regeneration Technology - Jintong Lv (International Journal of Public Health and Medical Research, 2026)
This study focuses on the mechanism of tooth tissue repair using stem cell regeneration technology, an interdisciplinary frontier in regenerative medicine and tissue engineering. Dental-derived mesenchymal stem cells, including Dental Pulp Stem Cells (DPSCs), Stem Cells from Human Exfoliated Deciduous Teeth (SHEDs), and Periodontal Ligament Stem Cells (PDLSCs), possess excellent proliferation ability and multi-directional differentiation potential, which provide a promising approach for functional repair of damaged dental tissues. This paper first reviews the research background, domestic and international research status of dental tissue repair, and clarifies the limitations of traditional repair methods. Then, the research objectives, core contents, and key scientific issues are elaborated, including clarifying the repair mechanism of different stem cells, constructing animal models of dental defects, and exploring the regulatory role of microenvironmental factors and signal pathways. Subsequently, the research methods such as stem cell isolation and identification, animal model establishment, and molecular biological detection techniques are detailed, and the feasibility of the research is analyzed. The research progress, preliminary results, and innovative points are also presented. Finally, the key findings of the study are discussed, and the limitations, clinical transformation prospects, and future research plans are prospected. This study aims to clarify the molecular mechanism of stem cell-mediated dental tissue repair, provide experimental basis for clinical translational research, and promote the development of personalized dental tissue regeneration strategies.